O processo repatriação na visão de profissionais repatriados brasileiros - Spohr, Nicole (2011)
The increasing internationalization has extended the number of expatriate employees, sent by companies to live and work abroad. Companies tend to believe that the repatriation, which is the return of these professionals to their home country, is easy, since the individual is returning home. However, problems associated with repatriation often causes the repatriates to leave the multinational that sent them abroad. Thant represents a significant loss of investments and knowledge created. Considering that repatriation has received little attention from academics, this research sought to examine how the process of repatriation occurred according to Brazilian returnees. Twenty repatriates from Brazilian and foreign companies were interviewed. Data analysis indicates that the repatriation process can be divided into five phases. Stages one and two occur in the foreign country of expatriation and the following ones happen in the home country. The first phase involves negotiating the position to be filled in Brazil once they return, while the second stage comprises the preparation for the return. Phase three - professional adjustment, back to the home country, involves the resocialization at the domestic unit. The fourth stage, personal adaptation, refers to the reorganization of domestic life and the last stage, called family adaptation, occurs only in cases where the family accompanied the expatriate during the assignment and involves the return of the spouse to the labor market and the children’s adjustment to school. From the analysis of policies and practices of repatriation, it seems that the emerging perspective is more appropriate to explain the retention of returnees. The findings suggest that even if the company does not support the employee during the international assignment, if it offers a suitable position after the return, there are fewer chances for the repatriate to leave. We conclude, therefore, that repatriation is a process, endowed with five stages, beginning in the foreign country and continued months after returning to the home country. With respect to policies and practices, they seem to be more of a logistical and financial matter than strategic. Nevertheless, only one interviewee left the company, which suggests that the satisfaction with the position held after the repatriation, which occurred in most cases, is the key to understanding the retention of returnees.